2020
DOI: 10.1111/ctr.13856
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, risk factors, and clinical outcomes associated with Epstein‐Barr virus‐DNAemia and Epstein‐Barr virus‐associated disease in patients after haploidentical allogeneic stem cell transplantation: A single‐center study

Abstract: Human leukocyte antigen (HLA)‐haploidentical hematopoietic stem cell transplantation (haplo‐HSCT) is an effective alternative to HLA‐matched transplantation. However, Epstein‐Barr virus (EBV) infection causes morbidity and mortality in patients undergoing haplo‐HSCT. Here, we retrospectively evaluated the incidence and risk factors of EBV‐DNAemia and EBV‐associated diseases in 131 patients who underwent haplo‐HSCT. Patients were classified into the no EBV infection groups, EBV‐DNAemia group and EBV‐associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
14
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 19 publications
(38 reference statements)
2
14
1
Order By: Relevance
“…In two studies, aGvHD was dichotomized in grade ≥3 versus <3; one of them (Juvonen et al [ 66 ]) showed that patients with aGvHD grade ≥3 had a higher risk of active EBV infection (HR = 1.70 (95% CI: 1.11–2.62)). However, this result was not corroborated by other studies [ 51 , 91 , 101 ]. Among eight studies [ 4 , 39 , 41 , 57 , 59 , 74 , 86 , 89 ] that compared grade ≥2 versus <2, two [ 59 , 89 ] showed that an aGvHD grade ≥2 significantly increased the risk of active EBV infection, one reported a positive association without reporting the relative risk (Hiwarkar et al [ 58 ]), and the other (Sirvent-Von Bueltzingsloewen et al [ 89 ]) reported an OR = 3.4 (95% CI: 1.2–9.7).…”
Section: Resultscontrasting
confidence: 99%
See 4 more Smart Citations
“…In two studies, aGvHD was dichotomized in grade ≥3 versus <3; one of them (Juvonen et al [ 66 ]) showed that patients with aGvHD grade ≥3 had a higher risk of active EBV infection (HR = 1.70 (95% CI: 1.11–2.62)). However, this result was not corroborated by other studies [ 51 , 91 , 101 ]. Among eight studies [ 4 , 39 , 41 , 57 , 59 , 74 , 86 , 89 ] that compared grade ≥2 versus <2, two [ 59 , 89 ] showed that an aGvHD grade ≥2 significantly increased the risk of active EBV infection, one reported a positive association without reporting the relative risk (Hiwarkar et al [ 58 ]), and the other (Sirvent-Von Bueltzingsloewen et al [ 89 ]) reported an OR = 3.4 (95% CI: 1.2–9.7).…”
Section: Resultscontrasting
confidence: 99%
“…Among the 62 articles included to analyze risk factors for post-transplant EBV infection, two relate exactly to the same patient cohort (Bogunia-Kubik et al [ 36 ] and Bogunia-Kubik et al [ 35 ]) and 11 relate to non-disjoint samples (include some of the same patients) (Cesaro et al [ 41 ] and Cesaro et al [ 42 ]; Liu et al [ 74 ] and Liu et al [ 27 ]; Xuan et al [ 99 ] and Liu et al [ 74 ]; Liu et al [ 75 ] and Liu et al [ 73 ]; Wang et al [ 97 ] and Ru et al [ 86 ]; Zhou et al [ 102 ] and Zhou et al [ 101 ]). However, none of these studies but one [ 101 ] were excluded from the qualitative synthesis for duplication because the risk factors explored were different. The study by Zhou et al [ 102 ] was excluded because all variables in this paper were explored using univariate analysis and were considered in the study by Zhou et al [ 101 ] using multivariate analysis.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations